Аnalysis of natural disasters and their impact on the environment - Azarov, Sergii I.; Zadunaj, Oleksii S. (Kyiv National University of Construction and Architecture, 2019)
Millions of lives could be saved if states did more to prevent and reduce the risks of natural disasters. Protecting people from all sorts of disasters and accidents – one of the priorities in many countries. The disasters that have occurred show that natural disasters have no boundaries and do not choose the people. Especially in recent years, the challenge of natural disasters, accompanied by climate change, floods, mudslides, earthquakes, droughts and fires, is increasing. The quantity and total damage of the natural disasters has increased in recent years. Global changes in the environment and climate, increasing levels of seismic activity of the Earth's crust, increasing the size and power of technical systems used, progressive human intervention in nature increase the risks of large-scale natural, environmental and man-made disasters. The rate of growth of economic losses from catastrophes is reaching the indicators of economic development of most developed countries and poses a global threat to the population, nature and the world economy. The article performs analysis of the natural disasters occurred in the world and their impact on environment. Knowledge of the causes, dynamics and nature of natural disasters can reduce the threat to life and health of people, prevent or reduce material and economic losses in business, effectively carry out a complex of preventive, rescue and emergency work associated with natural disasters.Analyzed the specific situation of occurrence of natural disasters. Particular attention is paid to assessing economic and social losses from natural disasters.